Factors relating to participation in follow-up to the 45 and up study in Aboriginal and non-Aboriginal individuals. Issue 1 (December 2016) - Gubhaju, Lina; Banks, Emily; Macniven, Rona; Joshy, Grace; McNamara, Bridgette; Bauman, Adrian; Eades, Sandra J.
Abstract Background This study aimed to characterise the factors relating to participation in a postal follow-up study in Aboriginal and non-Aboriginal individuals, given the need to quantify potential biases from loss to follow-up and the lack of evidence regarding postal surveys among Aboriginal people. Methods The first 100, 000 participants from the Sax Institute's 45 and Up Study, a large scale cohort study, were posted a follow-up questionnaire gathering general demographic, health and risk factor data, emphasising Social, Economic and Environmental Factors ("The SEEF Study"). For each variable of interest, percentages of those invited who went on to participate in follow-up were tabulated separately for Aboriginal and non-Aboriginal participants and age- and sex-adjusted participation rate ratios (aPRR) were calculated. Results Of the 692 Aboriginal and 97, 178 non-Aboriginal invitees to the study, 314 Aboriginal (45 %) and 59, 175 non-Aboriginal (61 %) individuals responded. While Aboriginal people were less likely to respond than non-Aboriginal people (aPRR 0.72, 95 % CI 0.66–0.78), factors related to response were similar. Follow-up study participants were more likely than non-participants to have university versus no educational qualifications (1.6, 1.3–2.0 [Aboriginal]; 1.5, 1.5–1.5 [non-Aboriginal]) and an annual income of ≥70, 000 versus < 20, 000 (1.6, 1.3–2.0; 1.2, 1.2–1.3 [χ 2 = 7.7;p = 0.001]). Current smokers (0.55, 0.42–0.72; 0.76, 0.74–0.77 [χ 2 = 7.14;p = 0.03]), those reporting poor self-rated health (0.68, 0.47–0.99; 0.65, 0.61–0.69), poor quality of life (0.63, 0.41–0.97; 0.61, 0.57–0.66) and very high psychological distress (0.71, 0.68–0.75 [non-Aboriginal]) were less likely than other cohort members to respond. Conclusions Relatively large numbers of Aboriginal and non-Aboriginal individuals participated in the first 45 and Up Study follow-up suggesting that postal surveys can be used to follow Aboriginal participants in cohort studies. Despite somewhat greater loss to follow-up in Aboriginal people (after considering socio-demographic and health characteristics), factors related to follow-up participation were similar in both groups: greater loss was observed in those experiencing disadvantage, ill-health and health risk, with implications for interpretation of future findings. Aboriginal low income earners and current regular smokers had a particularly elevated likelihood of non-participation compared to non-Aboriginal people. These findings highlight the importance of identifying and addressing barriers to participation among hard-to-reach population groups.